Quantifying transnational climate impact exposure: New perspectives on the global distribution of climate risk. (September 2018) - Hedlund, Johanna; Fick, Stephen; Carlsen, Henrik; Benzie, Magnus
Highlights: A framework for exposure to transnational climate impacts is proposed. A global index using quantitative indicators, statistical analyses and spatial representation is developed as a measurement of transnational climate impacts. The index shows a more complex spatial distribution of transnational climate impacts than current climate vulnerability indices. Policy-making on climate change adaptation should thus consider global interconnections between countries. Abstract: Indicators used in climate change adaptation planning are largely based on estimates of national or local climate vulnerability. However, classic vulnerability indices do not consider cross-border effects and global interconnections. We attempt to reconcile this need for a broader perspective by developing a global index of exposure to transnational climate impacts, which we define as impacts that are transferred via flows between countries. The index integrates traditional climate vulnerability indicators with spatially-explicit teleconnections between specific countries and constitutes a first approximation of the distribution of such exposure globally. Our results indicate that even though climate risks emerging from within a country's borders are highly correlated with economic development and geography, the distribution of exposure to transnational climate impacts provides a much more complex picture of global vulnerabilities, which neither geography, nor economic development alone can explain sufficiently. This highlights the need to take a cross-scale and multidimensional perspective of climate risk. In order to support more robust adaptation planning, risk assessments should consider both transboundary and far-reaching teleconnected interdependencies between countries.